Geology of the South-Eastern Richtersveld - Middlemost, Eric Arthur Kenelm (Department of Geological Sciences, 2023)
In their recent study or the geology of the, Richtersveld, de villiers and. Sohnge (1959) _have shown that ' the south-eastern ·part or this area is geologically complex, and contains numerous problems that can only be solved by detailed study. 'The .present investigation is an attempt - to find solutions ·to contoured geological -problems, as possible and thus increase our knowledge of the geology _of the lt1ehtersveld an area that forms a link between· the geology of the- western Cape and southwest Africa. During _ the present investigation a. contoured geological map of the south-eastern Richtersveld on a scale of 1:25,000, was constructed. 'Four hundred and graphic modal analyses ·were .made; and twenty-five chemical analyses were used, fourteen were new, and the remaining eleven were taken from the Richtersveld Memoir